Ordenamento Fundiário de Conceição do Araguaia – Pará: evolução do desmatamento no município e nas áreas de assentamentos rurais - Arraz, Rafael Miranda (Universidade Federal do Tocantins, 2023)
With human consumption needs the environment undergoes changes over the years, and can be reflected and characterized in the forms of land use and occupation. In that regard, anthropic actions in the environment are discussed as socioenvironmental problems. In the Brazilian Amazon and in the county region from Conceição do Araguaia – Pará, the process of land use and occupation has great influence of agribusiness practices, that over the past thirty-five years grew significantly.The purpose of this thesis was to understand how it was the land order of the 38 rural settlements (2,256 km²) and analyze the temporal dynamics of land use and occupation in the municipality of Conceição do Araguaia-PA, in the period from 1985 to 2020. The methodology of the approach is quantity and qualitative, with the use of bibliographical research and documentary, in addition to interviews semistructured, analyzed with the technique of Content Analysis (Enunciation), being carried out with public agents from INCRA, of ATERs, Union of Rural Workers and with their own family settlers who have experienced the struggles, achievements and challenges over the years in rural settlements investigated for a better understanding how it was the land order of this municipality. To analyze the evolution of deforestation in the municipality and in your Settlement Projects (PAs) survey was carried out of data by the Mapbiomas platform, that uses techniques of remote sensing to produce maps and tables with the portrait of land use and occupation through digital processing of satellite images that traces the forest loss in the time frame of 35 years. As results we have: the process of implementation of rural settlements of the municipality investigated came from spontaneous occupations, not being respected the environmental laws by most of the beneficiaries of rural properties and mainly due to omission by INCRA, because the state was absent in the respective rural settlements after their adjustments. In evolution land use and occupation in the evaluated time (1985 to 2020), the results showed that in comparisons in percentage proportion the loss of native vegetation, within PA areas it was considerably larger over the 35 years with 56%, than in relation to forest reductions from areas outside the PAs with 43%, from the entire municipality evaluated, being pointed out the activities agropastoral as the main cause of this forest loss.